AB0038 IMMUNE PHENOTYPING OF ERDHEIM-CHESTER DISEASE THROUGH MASS CYTOMETRY. (2nd June 2020) - Papo, M.; Corneau, A.; Cohen, F.; Robin, B.; Emile, J. F.; Miyara, M.; Blanc, C.; Amoura, Z.; Hermine, O.; Haroche, J.; Trovati Maciel, T.
Abstract : Background: The understanding of Erdheim-Chester Disease (ECD) pathogenesis has been greatly improved these past few years with the discovery of activating MAPK pathway mutations in most of ECD patients. However, the inflammatory phenotype of ECD remains widely unknown. Objectives: We aimed to explore the inflammatory phenotype of Erdheim-Chester disease (ECD) using mass cytometry. Methods: We analyzed peripheral blood mononuclear cells from 13 ECD patients and 11 healthy donors (HD) using mass cytometry with 29 metal-conjugated antibodies. Results: Compared to HD, untreated ECD patients had increased proportion of classical monocytes (90.8 [87.1-96.5] vs 81.6 [76.2-87.5] %, p=0.02) and decreased proportion of non-classical monocytes (4.7 [3.4-9.7] vs 11.8 [6.6-17.2] %, p=0.047). Untreated ECD patients had more circulating Th17 cells compared to HD (3.3 [3-5.3] vs 1.3 [0.4-2.3] %, p=0.015) and ECD patients treated with BRAF or MEK inhibitors (3.3 (3-5.3] vs 1.9 [0.6-2.4] %, p=0.005). Moreover Treg cells were lower in ECD patients than HD, with an increased Th17/Treg ratio (1.37 [0.74-1.9] vs 0.34 [0.19-0.43], p=0.0004). There was no difference regarding Th1 cells, Th2 cells, B cells, NK cells and circulating dendritic cells. Conclusion: ECD monocyte profile seems similar to what have been described in CMML. Inflammation observed in ECD may be driven through Th17 cells, and might be targeted with specific treatment. Disclosure of Interests: None declared